Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fpubh.2022.896843
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Exposure to COVID-19 and Mental Health Outcomes Among Healthcare Workers

Abstract: Due to the unprecedented impact of the COVID-19 pandemic on health care systems, there has been great interest in the mental wellbeing of healthcare workers. While most studies investigated mental health outcomes among frontline vs. non-frontline healthcare workers, little is known about the impact of various work-related variables. The present study aimed to examine the association between work-related [i.e., having contact with COVID-19 patients, being redeployed due to the pandemic and availability of suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 54 publications
0
17
1
Order By: Relevance
“… 34 In support of our findings, Czepiel et al reported that psychological distress, depressive and post-traumatic stress symptoms were associated with fears from infection among HCW. 35 Furthermore, a previous case-report of COVID-19-related concerns in HCWs has documented depressive and anxious symptoms in an HCW after spreading the infection to a family member. 36 …”
Section: Discussionmentioning
confidence: 99%
“… 34 In support of our findings, Czepiel et al reported that psychological distress, depressive and post-traumatic stress symptoms were associated with fears from infection among HCW. 35 Furthermore, a previous case-report of COVID-19-related concerns in HCWs has documented depressive and anxious symptoms in an HCW after spreading the infection to a family member. 36 …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of unfavourable mental health outcomes in our study is high compared to a similar study from another part of India where depression was reported among 47.4% of the HCWs, while anxiety and insomnia were seen among 29.0% and 32.2% of the participants respectively. 25 Similar studies conducted among the HCWs during the pandemic from different parts of the world have reported a prevalence of depression ranging from 8.9% to 77.2%, [7][8][9][10][11][12][26][27][28][29][30][31][32][33][34][35][36] anxiety 14.5% to 88%, [7][8][9][10][11][12][26][27][28][29][31][32][33][34][38][39][40][41] and insomnia 8.3% to 85.4%. 16,27,28,[30][31][32][33][34][35][36][37]…”
Section: Discussionmentioning
confidence: 99%
“…All the items are rated using a five-point Likert scale (0 = no problem; 4 = very severe problem), yielding a total score ranging from 0 to 28. The scores were interpreted as follows: Normal (0-7), subthreshold insomnia (8)(9)(10)(11)(12)(13)(14), moderate insomnia (15-21) and severe insomnia (22)(23)(24)(25)(26)(27)(28).…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations